MYCOPLASMA SPP. INFECTIONS AND MYOCARDIAL INFARCTION - I. P. Arleyevsky; O. A. Chernova; L. A. Ganeyeva; I. N. Safin; V. M. Chernov (Российский кардиологический журнал, 2003)
The article contains results of studies of clinical features of acute myocardial infarction in patients with Mycoplasma spp. infections; discussions of peculiarities in the development of the disease, as wells as possible mechanisms of atherogenesis induction in Mycoplasma spp. persistence.